VARIABEL EKONOMI MAKRO YANG MEMPENGARUHI PENERIMAAN PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR DI ACEH - Munawir Munawir; Abd. Jamal; Chenny Seftarita (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2017)
Motor vehicle tax and vehicle ownership changingtax are two of local tax that contributed greatly to the revenue of locally-generated revenue in Indonesia. This research aims to analyze the macroeconomic variables that influence revenue of motor vehicle tax andvehicle ownership changing taxof the province of Aceh.The variables suspected to affect revenue of motor vehicle tax and vehicle ownership changingtax in Aceh are the number of population,  economic growth and inflation. The periode which has been used in this case is starting on 2000 until 2015. In this study obtained data from Badan Pusat Statistik (BPS) and Badan Pengelola Keuangan Aceh (BPKA). From result of research indicate that: 1.The effect of the number of residents on the acceptance of PKB and BBNKB both show a positive value, but for PKB have a significant influence, while for BBNKB is not significant. 2. Influence of GRDP to PKB and BBNKB both show positive and significant value 3. Inflation Influence on PKB shows positive value but not significant, while inflation regression coefficient to BBNKB show negative and insignificant value.